2001
DOI: 10.1002/ajmg.1371
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of association of 13 polymorphisms in eight genes in southeastern African American Alzheimer disease patients as compared to age‐matched controls

Abstract: Alzheimer disease (AD) is an emotionally devastating and exceptionally costly disease. Apolipoprotein E (APOE) is a major risk factor gene for AD regardless of age of onset or family history. However, this association may not be as strong or consistent in ethnic groups such as African Americans, raising the possibility of other modifier gene(s). In a group of African American AD patients, a significantly increased risk of AD was associated with two E4 alleles (OR = 5.6; 95% CI = 1.5-21.0) or one E4 allele (OR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
1
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 109 publications
1
37
1
1
Order By: Relevance
“…However, a post hoc power calculation revealed that the present study has only sufficient statistical power to exclude an allele frequency difference of about 6% and the power is even less considering the fact that genegene interaction were investigated. Our data, however, support the findings of several other studies in which no increased AD risk was found to be associated with LRP1 CC genotype frequency [Woodward et al, 1998;Beffert et al, 1999;Bullido et al, 2000;Hatanaka et al, 2000;Hu et al, 2000;McIlroy et al, 2001;Perry et al, 2001;Sanchez-Guerra et al, 2001]. Kang et al [1997] also reported that, when APOE e4 homozygotes were left out of the analysis, the correlation between LRP1 gene and AD was strengthened.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…However, a post hoc power calculation revealed that the present study has only sufficient statistical power to exclude an allele frequency difference of about 6% and the power is even less considering the fact that genegene interaction were investigated. Our data, however, support the findings of several other studies in which no increased AD risk was found to be associated with LRP1 CC genotype frequency [Woodward et al, 1998;Beffert et al, 1999;Bullido et al, 2000;Hatanaka et al, 2000;Hu et al, 2000;McIlroy et al, 2001;Perry et al, 2001;Sanchez-Guerra et al, 2001]. Kang et al [1997] also reported that, when APOE e4 homozygotes were left out of the analysis, the correlation between LRP1 gene and AD was strengthened.…”
supporting
confidence: 91%
“…This result has been confirmed by some subsequent studies [Baum et al, 1998;Hollenbach et al, 1998;Kamboh et al, 1998;Lambert et al, 1998], although the strength of association with AD was not a particularly strong one. Contradictory results have been reported from other studies [Woodward et al, 1998;Beffert et al, 1999;Bullido et al, 2000;Hatanaka et al, 2000;Hu et al, 2000;McIlroy et al, 2001;Perry et al, 2001;Sanchez-Guerra et al, 2001], while some authors found an association between exon 3 LRP1 gene polymorphism and AD modulated by APOE e4 allele and gender [Bullido et al, 2000;Hatanaka et al, 2000].…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Thus, it is important to control for such variables in analyses examining racial differences in the effect of APOE genotype on CD. Moreover, it is of interest to note that in cross-sectional studies restricted to African American samples (thus decreasing between-group variability on SES and health variables) researchers have been more likely to find an association of APOE genotype and AD [24][25][26] .…”
mentioning
confidence: 99%
“…Isolation of genomic DNA and general procedures for PCR-RFLP genotyping have been described [74]. Reagents and conditions to amplify the XmnI polymorphism (C →T) at bp −158 of HBG2 were, 0.5 pmole each of left (5'-GCACTGAAACTGTTGCTTTATAGGAT-3') and right primers (5'-GCGTCTGGACTAGGAGCTTATTG-3'), 0.5 U of Taq (Promega, Madison, WI) and 37 cycles of 94°C/40 sec, 55°C/30 sec, 72°C/1 min.…”
Section: Xmni Genotyping Of -158 Polymorphism Of Hbg2 In the Nimh Ad mentioning
confidence: 99%